2004
DOI: 10.3168/jds.s0022-0302(04)70061-2
|View full text |Cite
|
Sign up to set email alerts
|

Rumen Development, Intestinal Growth and Hepatic Metabolism In The Pre- and Postweaning Ruminant

Abstract: Both the role of intestinal development and the process of transitioning calves from their neonatal reliance on nutrients supplied from milk to nutrients supplied from grain are of substantial economic importance to the producer. Improvements to the calf nutritional regime can decrease mortality and disease susceptibility, increase postweaning rate of gain, ultimately enhancing the rate of herd genetic improvement (due to increased capacity for voluntary culling). Current feeding practices including daily enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
484
2
32

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 502 publications
(536 citation statements)
references
References 78 publications
18
484
2
32
Order By: Relevance
“…Because the DMI was greater due to the addition of crude glycerin, the calves could be weaned earlier, which would result in lower feeding costs because concentrate is cheaper than milk or dried milk and also stimulates rumen development and contributes to supplying nutrients to animals (Baldwin et al, 2004;Suárez et al, 2006;Khan et al, 2007). Considering the intake of 700 g day −1 concentrate (Quigley III, 1996;Campos and Lizieire, 2000) to carry out weaning, the calves that received concentrate with 240, 160, 80, and 0 g kg −1 crude glycerin included could have been weaned at 40, 42, 44, and 46 days of age, respectively (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Because the DMI was greater due to the addition of crude glycerin, the calves could be weaned earlier, which would result in lower feeding costs because concentrate is cheaper than milk or dried milk and also stimulates rumen development and contributes to supplying nutrients to animals (Baldwin et al, 2004;Suárez et al, 2006;Khan et al, 2007). Considering the intake of 700 g day −1 concentrate (Quigley III, 1996;Campos and Lizieire, 2000) to carry out weaning, the calves that received concentrate with 240, 160, 80, and 0 g kg −1 crude glycerin included could have been weaned at 40, 42, 44, and 46 days of age, respectively (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated that solid feeds in particular concentrates are crucial for the development of the rumen of neonatal ruminants. Based on various reports Baldwin et al (2004) pointed out that neonatal ruminants fed solely on milk diets, display limited rumen development in terms of rumen weight, capacity and papilla growth during the initial months of life. In this study, late adaptation to concentrate feed and the relation between milk and concentrate feed intake can be explained by a mechanism "reticular groove" proposed by Ørskov et al (1970).…”
Section: Discussionmentioning
confidence: 99%
“…A chegada de grande quantidade de aminoácidos e gorduras ao intestino delgado pode gerar, por exemplo, um pico de somatostatina, resultando em inibição da secreção de hormônios e enzimas gastrintestinais e pancreáticas. Além disso, a somatostatina possui efeitos antiproliferativos, podendo retardar o desenvolvimento funcional da mucosa intestinal (Baldwin et al, 2004).…”
Section: Resultsunclassified